Single carrier variable rate scheme and modified carrier allocation over a wireless channel with carrier frequency offset. (25th March 2022) - Khan, Abdul Rauf; Kumar, Preetam
Summary: Cyclic Prefix Orthogonal Frequency Division Multiplexing (CP‐OFDM) is the backbone for the 5G, Internet of Things (IoT), and future generation wireless networks. However, OFDM is less localized in the frequency domain, and that's why more sensitive to carrier frequency offset (CFO). In this paper, different multicarrier variable rate schemes are evaluated in the presence of CFO. Additionally, variable rate schemes based on group orthogonal‐orthogonal frequency division multiple access (GO‐OFDMA) are discussed, and the effect of changing carrier allocation is examined. Different allocation schemes along with different variable rate schemes are verified in the presence of the CFO. Further for Up‐link variable rate application, single‐carrier scenario for the variable rate is proposed in this paper, and bit error rate (BER) performance is evaluated and compared with the variable rate GO‐OFDMA. Abstract : Cyclic Prefix Orthogonal Frequency Division Multiplexing (CP‐OFDM) is the backbone for the 5G, Internet of Things (IoT), and future generation wireless networks. In this paper, different multicarrier variable rate schemes are evaluated in the presence of CFO. Further for Up‐link variable rate application, single‐carrier scenario for the variable rate is proposed in this paper, and BER performance is evaluated and compared.